Lugenia Burns Hope and the neighborhood union: Culturally grounded community-based programming in the early twentieth century - Felecia C. Harris (Adult Education Research Conference, 1994)
This study extends the conceptual framework of traditional community-based programming models to include a culturally grounded community-based programming model developed during the early twentieth century by Lugenia Burns Hope and the Neighborhood Union (1908).